<span>The 6 means we round the 7 up to the next number which is 8. Thus, we round 4.76 to </span>4.8
Hello :
5a-5 +2a =2a
5a =5
a=1 ( refused)
conclusion : <span>none</span>
Answer:
The midsegment is one-half the length of the base
Answer:
(x + 9)(x + 3)
Step-by-step explanation:
Factor 27 so that the factors, when combined, will equal 12:
x² + 12x + 27
x 9
x 3
(x + 9)(x + 3) is your answer.
Check: Use the FOIL method. Multiply the first two terms, the outside terms, the inside terms, and then the last two terms. Combine like terms:
(x + 9)(x + 3) = x² + 3x + 9x + 27 = x² + 12x + 27 (√)
~